Changes in T-cell subpopulations in mice during prolonged experimental secondary infection with Echinococcus granulosus. Issue 4 (August 1995) - Rueda, M. C.; Osuna, A.; De Rycke, P. H.; Janssen, D.
Abstract : Balb/c mice were infected intraperitoneally with protoscoleces of Echinococcus granulosus . After 15 months of infection, and by means of flow cytometry, the expression of T-cell markers CD3, CD4, and CDS on T cells from peripheral blood, spleen, and thymus was analyzed and compared with that of age-matched controls. Infected mice had higher percentages of CD3+, and CD4+ cells in peripheral blood, and higher percentages of CD8+ cells in the spleen, when compared with control mice. CD4+ and CD8+ cells in peripheral blood and CD8+ cells in thymus also showed higher percentages of expression of interleukin-2 receptor. The results infer a role for interleukin-2 in experimental secondary echinococcosis.